The era of CFTR modulators: improvements made and remaining challenges. Issue 2 (June 2020) - Cuevas-Ocaña, Sara; Laselva, Onofrio; Avolio, Julie; Nenna, Raffaella
Cystic fibrosis (CF) is an autosomal recessive disorder caused by mutations in the CF transmembrane conductance regulator ( CFTR ) gene [1]. The CFTR protein is an ion channel that mediates chloride and bicarbonate transport in epithelial cells of multiple organs including lungs, pancreas and intestine [2, 3]. A defective CFTR protein produces an impaired ion and fluid secretion in the epithelial cells affecting several organs and leading to severe lung disease. More than 2000 CF-causing mutations have been identified [4, 5]. The most common mutation, the deletion of phenylalanine at position 508 (F508del), induces misfolding of the protein that is retained in the endoplasmic reticulum and degraded by proteasomal pathways [6]. The entry into the clinic of CFTR modulators such as TRIKAFTA has significantly improved life for ∼90% CF patients carrying one or two F508del mutations but challenges remain for rare CFTR mutations and the management of lung infections @SaraOcana1 https://bit.ly/3aRafQF